Multifunctional hydrophobic fabric-based strain sensor for human motion detection and personal thermal management. (1st March 2023) - Zhu, Tianxue; Liu, Lexin; Huang, Jianying; Li, Shuhui; Lei, Yonggang; Cai, Weilong; Lai, Yuekun; Li, Huaqiong
Graphical abstract: Image, graphical abstract Highlights: Sensors with multifunctional biomedical applications are rational designed and fabricated. The developed PDMS treatment enhances sensor's durability and stability. The smart fabric has excellent photothermal and Joule-thermal performance as thermal management device. Benefit from good anti-wetting and photothermal property, smart fabric exhibits superior de-icing ability. Abstract: Multifunctional flexible devices for human motion detection and thermal management raised great attention as the problem of the aging population is becoming more and more serious. However, it is still a challenge to endow the devices with excellent stability and wide application scope. Here we prepared a hydrophobic and conductive fabric-based strain sensor for smart fabric via successively coating with polydopamine (PDA), polyaniline (PANI), polypyrrole (PPy), and polydimethylsiloxane (PDMS) through in-situ polymerization and dip-coating, which could be used for strain sensor and wearable heater both in air and underwater. The obtained sample exhibited a fast electrical response in 500 ms and could withstand 10, 000 times stretching-releasing cycles, additionally, the sample exhibited satisfactory electro-thermal and photo-thermal performances. As a whole, the multifunctional fabric-based devices with excellent performances show great potential to be applied in medical monitoring and personal care, especially for aged and disabled persons.